Antimicrobial Susceptibility Patterns of Pseudomonas aeruginosa from Diabetes Patients with Foot Ulcers - Tamil Selvi Sivanmaliappan; Murugan Sevanan (International Journal of Microbiology)
Pseudomonas aeruginosa is an invasive organism that frequently causes severe tissue damage in diabetic foot ulcers. A major problem in P. aeruginosa infection may be that this pathogen exhibits a high degree of resistance to a broad spectrum of antibiotics. The study aimed to isolate and determine the antimicrobial susceptibility patterns of the P. aeruginosa population from diabetes patients with foot ulcers attending tertiary care hospitals in and around Coimbatore and their antimicrobial susceptibility pattern. The study was carried out at the Department of Microbiology, Dr. N.G.P. Arts and Science College, Coimbatore, for a period of one year (June 2006 to April 2007). The present study comprised 270 pus specimens collected from diabetic patients with foot ulcers. All pus samples were subjected to gram staining; bacterial culture and subsequently the antibiotic sensitivity to 15 different antibiotics for the confirmed P. aeruginosa were performed as per the standard procedures. Eighteen strains (14.28%) of P. aeruginosa from 270 diabetic foot ulcers were detected. Almost all the strains exhibited a varying degree of resistance to the antibiotics tested. Multidrug resistance for about 8 to 11 antibiotics was observed among the 55.5% of the isolates. Disk diffusion results show 100% resistance to ampicillin, cefoperazone, erythromycin, norfloxacin, and only cefotaxime, ciprofloxacin exhibited greater activity against Pseudomonas aeruginosa.